Природне право в консервативно-правовій думці Російської імперії кінця XIX - початку XX століть (Л. Тихомиров) - Прокопов, Д.Є. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Анализируется специфика осмысления понятия природного права и доктрины природного права в процессе становления консервативно-правовой мысли Российской империи в конце ХІХ - начале ХХ века. В качестве предмета исследования автор выбиает концепцию права одного из наиболее ярких представителей этой правовой традиции - Льва Тихомирова. The author investigates specificity of interpretation of the concept of natural law and its doctrines in the process of development of a conservative-legal thought of the Russian Empire at the end of nineteenth and beginning of the twentieth century. As a subject of research the author chooses the concept of the law and state of one of the brightest representatives of this legal tradition - Lev Tihomirov.